Unravelling the conceptualization of sexuality in Jeanette Winterson's The Passion and Written on the Body through Freudian and Foucauldian interpretations - Hamzah, Zarina (2012)
This study focuses on Jeanette Winterson’s conceptualization of sexuality in two of her novels, The Passion and Written on the Body. I argue that while sexuality has mainly been viewed as either biologically and physically determined or socially and culturally prescribed, Winterson approaches the subject with greater fluidity, avoiding too deep an attachment to either camp. Instead, Winterson at once acknowledges the material passion generated from human bodies and the conditioning of those bodies by social specificities, thus creating a type of sexuality that, at times, even defies distinctions of sex and gender. In other words, sexuality for Winterson is an ambiguous condition, or rather, an endless experience. Sigmund Freud and Michel Foucault can be deemed as sitting at opposite ends of the pole of sexuality, as it were. While Freud affirms that sexuality is inherent, an impulse and a physical manifestation of noumenal conditions, Foucault advocates the inevitable relationship between power and sexuality, wherein the latter works within a framework that involves culture, society and politics. But, I argue, understanding Winterson’s peculiar approach to sexuality is made clearer through both Freud’s and Foucault’s interpretations of sexuality, since she does not adhere to either strand but seems to build her own ideas of sexuality through supposed contradictions. Therefore, in this study, I propose to show, through a mobilization of Freud and Foucault’s theories of sexuality, how Winterson rejects simplistic distinctions thus far propounded within the discourse of sexuality. Following this, I attempt to draw out Winterson’s own lexicon of sexuality, one that both internalizes and externalizes issues such as passion, lust, love and desire. Finally, through her rejection of conventional notions of sexuality, out of which her unique lexicon of sexuality is generated, I argue that Winterson’s final purpose in breaking away from mere generalizations of sexuality is to affirm that sexual fluidity and honesty lead towards self-realization, a condition that is necessary for societal change and the possibility of change on a larger, more global scale.